Utopielyrik: Möglichkeitsdimensionen im poetischen Werk. Friedrich Hölderlin – Rainer Maria Rilke – Paul Celan - Hayer, Björn (transcript, 2021)
Poetry that breaks boundaries – Hölderlin's, Rilke's and Celan's poems united for the first time to form a new aesthetic movement: utopian poetry.